The effectivity of problem-based learning assisted by snakes and ladders games on students divergent thinking ability - Ghazian Nurin Izzati; Dwijanto Dwijanto; Adi Nur Cahyono (Jurnal Pijar Mipa, 2022)
This study aims to determine the effectiveness of problem-based learning assisted by the game of snakes and ladders on students' divergent thinking skills. The type of research is quasi-experimental, and it was conducted at a public junior high school in Semarang for the 2022/2023 academic year. The sampling technique in this study used purposive sampling, the population in this study was the entire class VIII, and the sample in the study was class VIII F as the experiment class (KF) and class VIII E as the control class (KE). The instrument used was a test result of student learning with five description questions, the hypothesis test used is one sample t-test, independent t-test, and z-test with sig 0.05. Based on the results of the study, it was found that the experimental class learning outcomes were higher than the control class learning outcomes. One sample t-test obtained that t count = 6.045 while t table = 0.683, so that t count > t table, it can be said that KF capability average exceeds 70, independent t-test obtained sig < 0.05 which is 0.001. The average of students with learning model problem-based learning with the help of snakes and ladders game on divergent thinking ability more than the average divergent thinking ability of mathematics. It can be said that 75% of students in the experimental class completed it classically. Learning with problem-based learning assisted by snake and ladder games on the students' divergent thinking skills was effective for the mathematics learning outcomes of class VIII students.